MediVerse : Challenges And Development Of Digital Health Transformation Towards Metaverse in Medicine - Yoesoep Edhie Rachmad (Journal of Engineering, Electrical and Informatics, 2022)
The development of telemedicine and telemedicine to digital health applications, the trend in cyberspace is the use of digitally virtualized social networks. Metaverse is based on the use of technology that enables multisensory interactions between virtual, digital objects and humans. Metaverse is supported by the use of Augmented Reality, Virtual Reality, Cloud Computing, Artificial Intelligence, Health Information Systems technology. This research aims to analyze, evaluate, and test the role of MediVerse in the challenges and development of the transformation of digital health services to the Metaverse in Medicine. This research used 624 informants in five regions of Indonesia with the highest Covid-19 cases, namely DKI Jakarta, West Java, Central Java, East Java and East Kalimantan in the period July 2021 to January 2022. The conclusions of this research are: (1) 624 respondents expressed that they are very satisfied with the current digital medical scenario and the need to implement Metaverse in medicine. This issue shows the potential benefits and importance of the application of Metaverse in Medicine in medical diagnosis, patient monitoring, healthcare training, surgery, medical therapy, and Theranostics. (2)The government is expected to support the progress and development of virtual digital systems in the Metaverse in Medicine in facing the challenges of the second stage of the Covid-19 pandemic, because it does not rule out the possibility that the Covid-19 outbreak will occur again in the next 3-4 years.